Harmony in the Hybrid Era: Digital Competence and Work Life Balance Create Exceptional Resilient Human Resources - Budi Harto; Tjutju Yuniarsih; Ade Sobandi; Disman; Arief Yanto Rukmana; Teti Sumarni (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of the digital startup ecosystem has transformed the labor market, creating a demand for resilient and adaptive human resources. Hybrid work arrangements and digital competencies are crucial in this context, yet their impact on human resource resilience, with work-life balance as a mediator, remains underexplored. This study aims to examine the effects of hybrid work and digital competence on human resource resilience in digital startups while investigating the mediating role of work-life balance. A quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis was employed on a purposive sample of 150 employees from digital startups in Bandung, with data collected through structured questionnaires measuring hybrid work, digital competence, work-life balance, and human resource resilience. Results indicate that hybrid work and digital competence significantly influence human resource resilience, with work-life balance partially mediating these effects. The proposed model explains 83.4% of the variance in human resource resilience and 60.5% of the variance in work-life balance. These findings underscore the necessity of integrated policies that combine hybrid work, digital competency development, and work-life balance enhancement to foster sustainable human resource resilience in digital startups.